Law enforcement slang - Rusanova, L. I.; Sazanova, L. S. (Кропивницький : РВВ ЦДПУ ім. В. Винниченка, 2021. С. 341 –343, 2021)
The theses consider the use of informal language (slang) by certain social groups of people (the police). The popularity of the use of slang terms, idioms, abbreviations which sometimes have an offensive connotation has been determined. It is confirmed that slang determines the experience of generational culture and allows groups of people to communicate and understand each other.
Keywords: law enforcement slang, social group, development of language, acronym, abbreviation, special code, slang nickname, complex dynamic phenomenon